Comparative Study of Self-Ligating Brackets and Conventional Brackets in Treatment Duration. A Clinical Study - Faryal Ali Syed, Junaid Tariq, Ayesha Yasir, Samina Qadir, Ahmad Shamim Qureshi, Beenish Elahee Rizvi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Advances in orthodontic appliance design have introduced self-ligating brackets as an alternative to conventional systems, claiming improved treatment efficiency and reduced duration. However, clinical evidence comparing both systems under standardized conditions remains limited. Objective: To compare the overall treatment duration, chairside time, and number of visits between self-ligating and conventional bracket systems in patients undergoing fixed orthodontic therapy. Methods: This prospective comparative clinical study was conducted in the Department of Orthodontics, Baqai Dental College, Karachi, from January 2022 to March 2023. A total of 150 patients, aged 14–28 years, were randomly allocated into two equal groups: Group A (self-ligating brackets) and Group B (conventional brackets). Both groups followed identical archwire sequences and clinical mechanics. The treatment duration (in months), chairside time (in minutes), and total number of visits were recorded. Data were analyzed using SPSS v26, and statistical significance was set at p < 0.05. Results: Patients treated with self-ligating brackets completed therapy in a significantly shorter mean duration (15.8 ± 3.5 months) compared to the conventional group (19.4 ± 4.1 months, p < 0.001). The mean chairside time per visit and total number of appointments were also significantly reduced in the self-ligating group (13.9 ± 2.4 minutes, 13.4 ± 2.0 visits) versus the conventional group (19.1 ± 3.6 minutes, 17.2 ± 2.8 visits, p < 0.001). Conclusion: Self-ligating brackets significantly reduce overall orthodontic treatment duration, chairside time, and number of visits compared with conventional brackets, without compromising final treatment quality. These findings highlight their clinical efficiency and potential to enhance both patient convenience and practice productivity. Keywords: Orthodontics, self-ligating brackets, conventional brackets, treatment duration, clinical efficiency, friction mechanics.